Strategi Peningkatan Literasi Membaca Melalui Pendekatan Whole Language Pada Siswa Kelas IV Di UPT SD Negeri Sinar Mulyo - Asyari, Nikola; Budi Prasetyo, Krisno (Fakultas Tarbiah Institut Agama Islam (IAI) Hamzanwadi Pancor Lombok Timur, 2025)
This study aims to describe the strategy for improving reading literacy using the Whole Language approach for fourth-grade students at UPT SD Negeri Sinar Mulyo. The background of this study is based on the low interest and understanding of students in reading, as well as the need for meaningful and enjoyable reading learning methods. This type of research is descriptive qualitative with a naturalistic approach, where researchers play a direct role in collecting data in the field. The subjects of the study consisted of fourth-grade teachers, students, and principals. Data collection techniques used include observations of the reading learning process in the classroom, semi-structured interviews with teachers and students, and documentation in the form of lesson plans, student work, and teacher reflection notes. The data obtained were analyzed using the interactive analysis technique of the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. Data triangulation was carried out to ensure the validity of the research results. The results showed that teachers implemented the Whole Language approach through various strategies such as reading together, discussing reading content, writing responses, role playing, and creating visualizations of story content. Students showed an increase in their ability to understand texts, confidence when reading, and higher interest in reading. The main constraints are limited time and reading materials, but can be overcome with a differentiation approach and the use of external sources. The conclusion of this study is that the Whole Language approach is effective in improving elementary school students' reading literacy because it emphasizes context, meaning, and active student involvement in learning. Keywords: Reading literacy, Whole Language approach, learning strategies, grade IV elementary school, contextual learning.